(3hXGFa GdSjGSI GdGbJUGOjI GdYGeI aj GdGbJUGO GdGSdGej (B/s - (3YfGjI, ZGRjs ((3YeGf(B: s (3OGQ GdefGgL ddfTQ h GdJhRjY(B, s, 2008)
(3GdJONd GdhXjaj GdGbJUGOj ddSjGSI GdGbJUGOjI GdGSdGejI, GdOhQ GdhXjaj GdGbJUGOj ddSjGSI GdGbJUGOjI GdGSdGejI(B: (3GdSjGSI GdGbJUGOjI GdGSdGejI hJehjd GdGSJKeGQ GdJfehj, GdSjGSI GdGbJUGOjI GdGSdGejI hJehjd GdGfJGL, GdSjGSI GdGbJUGOjI GdGSdGejI hJehjd GdeQGab GdJbdjOjI, GdSjGSI GdGbJUGOjI GdGSdGejI hJehjd JhXja GdehGQO, GdSjGSI GdGbJUGOjI GdGSdGejI hJehjd GdOhQI GdfbOjI, GdOhQ GdhXjaj GdGLJeGYj ddSjGSI GdGbJUGOjI GdGSdGejI(B: (3GdSjGSI GdGbJUGOjI GdGSdGejI hJMbjb CZQGV GdJfejI GdGLJeGYjI, GdSjGSI GdGbJUGOjI GdGSdGejI hJMbjb CZQGV GdVeGf GdGLJeGYj, GdSjGSI GdGbJUGOjI GdGSdGejI hJMbjb CZQGV GdJcGad GdGLJeGYj, GdOhQ GdhXjaj GdeGdj ddSjGSI GdGbJUGOjI GdGSdGejI, GdOhQ GdhXjaj GdSjGSI ddSjGSI GdGbJUGOjI GdGSdGejI(B: (3GdOhQ GdhXjaj GdSjGSj ddRcGI, GdOhQ GdhXjaj GdSjGSj ddVQGFH, GdOhQ GdhXjaj GdSjGSj ddfabGJ GdYGeIs
(3HHdjhZQGajG(B: (3U(B.207s
Keywords: (3GdGSJKeGQs; (3GdGbJUGO GdGSdGejs; (3GdGfJGLs; (3GdJNWjW GdGbJUGOjs; (3GdVQGFHs